Students quality of life in off-campus living enviroment: case study of UiTM Shah Alam / Muhammad Hilmy Muslim - Muslim, Muhammad Hilmy (2017)
Off-campus students are currently facing huge challenges associated with their living environment. Current trend of off-campus living environment are impacting students' Quality of Life. Residential satisfaction is an assessment of individual towards his dwelling, and it is a major criterion to represent the Quality of Life. This research aims to produce residential satisfaction criteria for Non-Resident (NR) students living in off campus environment. The data for this study use both qualitative and quantitative methods comprising key informant interview and questionnaire survey. The feedback of key informant interview are^used to get idea and used in drafting survey questionnaire. The questionnaire survey utilised a stratified sample of individuals with self-reported questionnaire which are directed to 341 NR students; in seven groups of neighbourhood namely: Seksyen 2 and Seksyen 3 (Nl); Seksyen 4 and Seksyen 6 (N2); Seksyen 7 (N3); Seksyen 8 (N4); Seksyen U12 (N5); Seksyen 16 and Padang Jawa (N6); and Seksyen 17 (N7) in the city of Shah Alam. Two types of analysis are used, that are Factor Analysis and Analysis of Variance (ANOVA). The result shows that out of seven criteria used to determine students' residential satisfaction in off-campus living environment, the most important criteria is neighbourhood surroundings; followed by dwelling setting; social interaction and social activities; recreational facilities; transportation services; neighbourhood attachment; and lastly public services. The research has contributed in two ways: first, it provides a clear and objective information on students' residential satisfaction; second, this research provides the criteria that can be used to assess the off-campus students' satisfaction level of their living environment.